Serial chest CT in cryptogenic organizing pneumonia: Evolutional changes and prognostic determinants. Issue 3 (27th September 2017) - Chung, Man P.; Nam, Bo D.; Lee, Kyung S.; Han, Joungho; Park, Jai S.; Hwang, Jung H.; Cha, Min J.; Kim, Tae J.
ABSTRACT: Background and objective: Cryptogenic organizing pneumonia (COP) is corticosteroid responsive but residual computed tomography (CT) chest changes are often noted. The present study examined clinical and HRCT features of COP in which there was incomplete resolution. Methods: We studied 93 patients with histopathologically confirmed COP and serial HRCT imaging. Clinical features were assessed, and serial CT images were analysed. Uni‐ and multivariate analyses were performed to determine clinical or imaging factors related to incomplete resolution on CT. Results: Complete resolution on CT imaging was seen in 21/93 patients (23%) and residual abnormalities were seen in 72/93 patients (77%). In univariate analysis, total lesion ( P  = 0.036), degree of consolidation ( P  = 0.011), treatment duration ( P  < 0.001) and single‐breath carbon monoxide diffusing capacity of lung ( P  = 0.021) were significantly associated with residual imaging abnormalities. In multivariate analysis, extent of consolidation ( P  = 0.018; odds ratio (OR) = 14.92) and treatment duration ( P  = 0.011; OR = 1.32) remained as significant factors linked to residual abnormalities. CT images in unresolved COP were akin to fibrotic non‐specific interstitial pneumonia (fNSIP) in 53/72 (74%) patients. Conclusion: Clinical, radiological and lung diffusion measurements were related to incomplete resolution on CT after COP. Imaging abnormalities on CT chest generally resembled fNSIP. Abstract : In patients with cryptogenic organizing pneumonia, 77% had residual computed tomography (CT) abnormalities on follow‐up CT chest, even after corticosteroid treatment. The extent of lung abnormalities, consolidation on CT, diffusion measurements and treatment duration were factors associated with residual CT abnormalities.